2011
DOI: 10.5209/rev_sjop.2011.v14.n1.28
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Body Dissatisfaction Relative to Gender and Age: The Modulating Character of BMI

Abstract: This study examines the level of body satisfaction in adolescents, and its association with age, sex and body mass index. A non-clinical group was made up of 935 adolescents (484 boys and 451 girls), aged between 10 and 18 years. The body image was assessed by the Body Dissatisfaction scale within the Eating Disorder Inventory (Garner, 1998, 2004) and by the indirect indicator Ideal Body Mass Index. The results showed that the Body Mass Index is an important covariable in the study of body dissatisfaction. Bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
21
1
11

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 34 publications
(40 reference statements)
7
21
1
11
Order By: Relevance
“…As a matter of fact, it has been found that men report greater antifat attitudes than women (Crandall, 1994). Other works show that men report less body dissatisfaction (Bully & Elosua, 2011) and eating concerns (Meyer, McPartlan, Rawlinson, Bunting, & Waller, 2011) than women. Additionally, there are studies that reveal that there is a link between ideology, like Right Wing Authoritarianism, Believe in a Just World or Modern Racism, and antifat attitudes (Crandall, 1994), and between gender related ideologies and antifat attitudes (Perez, Lewis, & Cash, 2001) which suggests that gender male ideologies may be related to thinness externalization although there are not studies analyzing it so far.…”
Section: Internalization-externalization Hypothesismentioning
confidence: 91%
“…As a matter of fact, it has been found that men report greater antifat attitudes than women (Crandall, 1994). Other works show that men report less body dissatisfaction (Bully & Elosua, 2011) and eating concerns (Meyer, McPartlan, Rawlinson, Bunting, & Waller, 2011) than women. Additionally, there are studies that reveal that there is a link between ideology, like Right Wing Authoritarianism, Believe in a Just World or Modern Racism, and antifat attitudes (Crandall, 1994), and between gender related ideologies and antifat attitudes (Perez, Lewis, & Cash, 2001) which suggests that gender male ideologies may be related to thinness externalization although there are not studies analyzing it so far.…”
Section: Internalization-externalization Hypothesismentioning
confidence: 91%
“…Hal ini tidak sesuai dengan penelitian yang dilakukan oleh Thomas et al (22) bahwa sebagian besar responden memiliki persepsi tubuh yang positif, hal ini mungkin disebabkan terdapat perbedaan kategori usia dengan yang dilakukan oleh peneliti yaitu pada penelitian Thomas et al (22) sebagian besar responden adalah dewasa muda dan memiliki kepercayaan diri yang tinggi sehingga dalam setiap kategori status gizi, sebagian besar memiliki persepsi tubuh yang positif. Hasil penelitian yang dilakukan oleh peneliti menyatakan bahwa sebagian besar responden memiliki persepsi tubuh yang negatif, hal ini didukung oleh penelitian yang dilakukan oleh Bully et al (23) , hal ini mungkin disebabkan pada penelitian Bully et al (23) dan penelitian ini sama-sama menggunakan kuesioner dan responden yang diteliti memiliki kategori usia yang sama yaitu pada kategori usia remaja. (23) Pada tabel 4.…”
Section: Pembahasanunclassified
“…Hasil penelitian yang dilakukan oleh peneliti menyatakan bahwa sebagian besar responden memiliki persepsi tubuh yang negatif, hal ini didukung oleh penelitian yang dilakukan oleh Bully et al (23) , hal ini mungkin disebabkan pada penelitian Bully et al (23) dan penelitian ini sama-sama menggunakan kuesioner dan responden yang diteliti memiliki kategori usia yang sama yaitu pada kategori usia remaja. (23) Pada tabel 4. Terlihat bahwa terdapat hubungan yang bermakna antara persepsi tubuh dengan eating disorders.…”
Section: Pembahasanunclassified
“…Elosua (2013) classifi ed the levels if dissatisfaction according to sex and age, fi nding that there is a higher dissatisfaction with body image among women, teenagers (ages 10 to 18) being the ones with most problems with perception of their bodies; 15 years old were the group with higher risk. In adult women (ages 19 to 20) levels of dissatisfaction are more leveled, although not completely (Bully & Elosua, 2011).…”
Section: Investigations Considering the Age Of The Womenmentioning
confidence: 99%